Pengaruh Terpaan Iklan dan Kredibilitas Brand Amabssador Raditya Dika terhadap Minat Mengunduh Aplikasi Game Last War: Survival - Adila Salsabila; Yanuar Luqman (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The mobile gaming industry in Indonesia has experienced rapid growth, triggering intense competition and compelling app developers to implement aggressive marketing strategis. This study aims to examine and analyze the influence of advertising exposure and the credibility of brand ambassador Raditya Dika on the download intention for the mobile game Last War: Survival. The theoretical framework utilized in this research includes mere exposure theory to explain the advertising exposure variable and source credibility theory for the brand ambassador credibility variable. This study employs a quantitative approach with an explanatory research design. Data were collected through a questionnaire survey of 167 respondents from Generation Z (aged 18-27) in Indonesia who had been exposed to Last War: Survival advertisements featuring Raditya Dika. The results show that both advertising exposure and brand ambassador credibility have a positive and significant influence on download intention, both partially and simlutaneously. However, brand ambassador credibility demonstrates a more dominant influence than advertising exposure, indicating that a credible message source is more effective in shaping audience intention than advertising frequency alone. Audience download intention was also found to be strong across transactional, referential, preferential and explanatory dimensions. These findings indicate that the effectiveness of digital marketing is determined not only by the intensity of advertising exposure, but also by the credibility of the public figure delivering the advertising message.